Implications of E-Learning of the Ministry of Religion on Student Learning Motivation in Islamic Religious Education Subjects at Madrasah Aliyah Daruttaqwa Gresik - Ulfa Indah (Journal of Social Research, 2023)
Focus in terms of research researchers analyzes the Implications of the Ministry of Religion's E-Learning on Students' Learning Motivation In Islamic Religious Education Subjects. This type of research is qualitative research with a descriptive approach and also a search with a case study approach. Because of online learning Teachers are required to think creatively and innovative so that students do not feel bored with studying e-learning. Besides that, there is also an impact with studying e-learning which results in changes in student motivational behavior in studying during the e-learning. The aims of this research are: 1) to analyze and describe the implementation of the Ministry of Religion's e-learning study Daruttaqwa Senior High School Gresik. 2) to analyze and describe studying implications of Minister try of Religion's e-learning on student learning motivation in Islamic religious education subjects at Daruttaqwa Senior High School Gresik. The results of the research at Daruttaqwa Senior High Schoolresik are 1) the learning process using the e-learning application of the Ministry of Religion which before starting learning the teacher councils must develop a method and creative and innovative learning media. Sometimes all teacher’s council also uses WhatsApp groups, google classroom, and youtube videos. 2) From the data obtained, it shows students learning motivation decreased because the teacher could not directly control when students learn, students feel bored during online learning, students often ignore assignments when submitting assignments.